Pengaruh Substitusi Tepung Ikan dengan Hidrolisat Bulu Ayam terhadap Penampilan Produksi Broiler - E. Kusnadi (Universitas Andalas, 2006)
An experiment was conducted to evaluate the effect of substitution of fish meal with hydrolyzed feather-meal in diet on the performances of broiler of 2-6 weeks of age. The treatments consisted of five levels of hydrolyzed feather-meal: 0, 4, 8, 12 and 16% in ration as B0, B4, B8, B12 and B16 respectively. The data collected were analyzed with a completely randomized design of 5 X 4 (5 levels of hydrolyzed feather-meal and 4 replications) and continued with contrast-orthogonal test when available. The results indicated that the level of hydrolyzed feather-meal significantly (P< 0.05) decreased the feed consumption, but the abdominal fat content and caucus weight were not significantly affected. The body weight gain of A4 was found not significantly different with that of control (B0) (1407.5 vs. 1331.00 g), but higher than that of B8 (1195.50), B12 (1118.75 g) and B16 (860.25 g).